2013 IEEE 7th International Conference on Self-Adaptive and Self-Organizing Systems 2013
DOI: 10.1109/saso.2013.20
|View full text |Cite
|
Sign up to set email alerts
|

Learning to be Different: Heterogeneity and Efficiency in Distributed Smart Camera Networks

Abstract: In this paper we study the self-organising behaviour of smart camera networks which use market-based handover of object tracking responsibilities to achieve an efficient allocation of objects to cameras. Specifically, we compare previously known homogeneous configurations, when all cameras use the same marketing strategy, with heterogeneous configurations, when each camera makes use of its own, possibly different marketing strategy. Our first contribution is to establish that such heterogeneity of marketing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…This is again based on the difficulty of capturing the global goals of overlap/redundancy, proportion of tracked objects, and total confidence by using only local information. This is an instance of the problem of decomposing global goals into local rewards, when assuming decentralisation, as discussed in a related problem by Lewis et al [11], [12]. It is also important to note that our results are not perfectly even distributed in the solution space.…”
Section: )mentioning
confidence: 86%
“…This is again based on the difficulty of capturing the global goals of overlap/redundancy, proportion of tracked objects, and total confidence by using only local information. This is an instance of the problem of decomposing global goals into local rewards, when assuming decentralisation, as discussed in a related problem by Lewis et al [11], [12]. It is also important to note that our results are not perfectly even distributed in the solution space.…”
Section: )mentioning
confidence: 86%
“…Hence, each agent should reason and act based on its own view and experiences. The opposite extreme, termed maximal knowledge access, is less common with only 8 studies [29], [31], [35], [62], [65], [72], [75], [76]. Here, all agents share complete knowledge with each other aiming to achieve the highest possible benefit for the collective.…”
Section: A Rq1: Csas Characteristics 1) Application Domain and Agentsmentioning
confidence: 99%
“…An interesting outcome of our review is the following. In several studies [30], [35], [36], [39], [43]- [45], [48], [49], [53], [61], [63], [69], [70], the system is designed in a way that each individual selfish agent learns a "learning task" and is not aware of the fact that it is collaborating. In these circumstances, the emergent behaviour of the system is the result of the agents' unaware collaboration and is often a system-wide collaboration scheme achieving a global goal.…”
Section: ) Behaviourmentioning
confidence: 99%
“…Their algorithm runs in a decentralized manner. Recently, Lewis et al [2013] have shown that the object tracking confidence improves when adopting heterogeneous marketing strategies by reducing the number of message exchanged. They have also shown that online learning of marketing strategies can achieved to find the suitable strategy for individual cameras.…”
Section: Market-based Approachmentioning
confidence: 99%